Molecular analysis of "de novo" purine biosynthesis in solanaceous species and in Arabidopsis thaliana - Sonnewald, Uwe; et al. (Frontiers in Bioscience, 2004)
The cloning of the genes involved in the purine biosynthesis pathway was attained by a screening strategy with heterologous cDNA probes and by using S. cerevisiae mutants for complementation. Southern hybridization showed a complex genomic organization for these genes in solanaceous species and their organ- and developmental specific expression was analyzed by Northern hybridization. The specific role of ATase for plant growth and development was analyzed in transgenic tobacco plants exhibiting a reduced ATase activity and in an Arabidopsis T-DNA mutant (atd2) deficient for ATase2. The transgenic tobacco plants as well as the Arabidopsis mutant exhibit a specific and comparable phenotype, which is characterized by strong growth retardation and severe chlorosis in leaves. The formation of white leaves, but green cotyledons is a characteristic trait of the Arabidopsis atd2 mutant.
Keywords: "de novo" purine biosynthesis; plant nucleotide metabolism; purine nucleotides; Solanacea; Arabidopsis thaliana; transgenic plants; T-DNA mutant; PRPP amidotransferase